Climate Change and Fiscal Response: Analysis of Regional Expenditure in Java Island - Amin, Muhammad Ikhsanul (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study investigates the impact of climate change on regional fiscal policy in Java, Indonesia, focusing on how temperature and rainfall changes influence fiscal spending. Using secondary data from the ERA5 Satellite (2008–2020) and fiscal data from the Directorate General of Fiscal Balance (Direktorat Jenderal Perimbangan Keuangan/DJPK), this research examines 113 districts/cities on Java Island. Climate change indicators—average temperature and rainfall—serve as independent variables, while regional fiscal spending on climate-related initiatives is the dependent variable. Panel data analysis is conducted using three regression models: common effect (OLS), fixed effect, and random effect models, with the Chow and Hausmann tests to identify the most appropriate model. Results indicate a positive relationship between climate change (temperature and rainfall) and increased fiscal spending for climate adaptation and mitigation. The findings support the hypothesis that regions with higher temperatures and increased rainfall experience greater climate-related fiscal spending, highlighting the urgency for such measures in areas farther from the equator.